The Effect of Financial Distress and Corporate Social Responsibility on Tax Avoidance (Case Study of Manufacturing Companies in the Pharmaceutical Sub-Sector Listed on the Indonesia Stock Exchange for the years 2017-2021 Period) - Sela Ainur Ramadani (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to examine the effect of financial distress and corporate social responsibility on tax avoidance in the pharmaceutical manufacturing subsector during the period of 2017-2021. The population of this study consists of pharmaceutical manufacturing companies. The research methodology employed is quantitative. The data used for this study were obtained from the website www.idx.co.id and annual reports that have been audited for each year, accessible through the official websites of the respective companies. Data collection was conducted using purposive sampling, with a total sample size of 30 data points over a 5-year observation period. The collected data were analyzed using SPSS version 25 for Windows. The results of the analysis indicate that the variable of financial distress does not have a significant effect on tax avoidance, while the variable of corporate social responsibility has a negative effect on tax avoidance.